2008
DOI: 10.1175/2007jtecha958.1
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Samplings and Remote Sensing Measurements to Characterize Aerosol Properties over Southeast Italy

Abstract: Ground-based particulate matter (PM) samplers, an XeF Raman lidar operating in the framework of the European Aerosol Research Lidar Network (EARLINET), and a sun/sky radiometer operating in the framework of the Aerosol Robotic Network (AERONET) have been used to characterize vertical profiles, optical and microphysical properties, and chemical composition of aerosols during the 29 June-1 July 2005 dust outbreak that occurred over the central-eastern Mediterranean. Aerosol backscatter coefficient, total depolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…This fact is suggested by the relatively high Angström exponent (α) values -measured after medium-long range dust transport in comparison with those obtained in source areas -and confirmed by analyses of chemical composition of ground-collected particles (e.g. Bellantone et al, 2008;Carofalo et al, 2008). Thus, several authors have pointed out the importance of taking into account the influence of anthropogenic particles on the direct radiative forcing associated with African desert dust intrusions over the Mediterranean basin and continental Europe (e.g., Gerasopoulos et al, 2003;Perrone and Bergamo, 2011).…”
Section: Introductionmentioning
confidence: 69%
“…This fact is suggested by the relatively high Angström exponent (α) values -measured after medium-long range dust transport in comparison with those obtained in source areas -and confirmed by analyses of chemical composition of ground-collected particles (e.g. Bellantone et al, 2008;Carofalo et al, 2008). Thus, several authors have pointed out the importance of taking into account the influence of anthropogenic particles on the direct radiative forcing associated with African desert dust intrusions over the Mediterranean basin and continental Europe (e.g., Gerasopoulos et al, 2003;Perrone and Bergamo, 2011).…”
Section: Introductionmentioning
confidence: 69%
“…The underestimate of sulfate and carbon particle concentrations representing the main anthropogenic aerosol components of local origin and/or long-range transported from industrialized areas (e.g. Bellantone et al, 2008;Santese et al, 2008) may also be responsible for the underestimation of AODs mainly at sites far away from dust sources. In this respect, it is worth noting from Fig.…”
Section: Overview Of July 2003 African Dust Intrusion Episodesmentioning
confidence: 99%
“…Pavese et al, 2008). The underestimate of the anthropogenic aerosol amount also may represent a contributing factor: morphological and elemental analyses on particulate matter samples collected at Lecce show that the anthropogenic fine mode aerosol, mainly composed of nitrate, sulfate, and carbon particles, can represent more than 50% of the aerosol load even during dust outbreaks (Bellantone et al, 2008).…”
Section: Comparison Of Simulated and Measurement-based Vertical Profimentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent Sahara dust event study by complementary remote sensing measurements and ground observations revealed that the anthropogenic fine mode aerosol was over south-east Italy more than 50% of the total aerosol load during a dust outbreak (Bellantone et al, 2008). η values smaller than 0.5 were generally retrieved both at Lampedusa and Crete during dust outbreaks.…”
Section: Analysis Of Aod Andå Data For All Sectorsmentioning
confidence: 99%